Gland Suspension Improves Breast Augmentation Outcomes. Issue 11 (November 2018) - Andjelkov, Katarina; Sijan-Miskovic, Nina; Colic, Milan; Colic, Miodrag; Lalic, Anja; Llull, Ramon
Abstract : Background: While dual plane breast augmentation successfully addresses low ptosis grades, concomitant hypomastia and greater ptosis often requires combined immediate or staged mastopexy with extended incisions beyond those required for breast augmentation. In an attempt at offering a minimal scar in a single procedure, we evaluated the benefit of a gland suspension maneuver in addition to a dual plane dissection and implant placement to improve breast contour, avoid postoperative ptosis, and thus reduce staged reintervention procedures. Methods: A consecutive group of 73 patients presenting ptotic hypomastia were jointly categorized and underwent implant placement, dual plane dissection level 3, and gland suspension maneuver. An age, implant volume, ptosis degree matched historical cohort was used as control (no gland suspension). All subjects were followed longer than 1 year postoperatively. Outcome analysis included reintervention rates and objective geodesic changes using objective morphometric parameters as measured by 3D scan analysis. Results: When experimental and control cohorts were segregated according to ptosis grade, gland suspension maneuver was associated to a lower frequency of subsequent ancillary mastopexy procedures (reintervention rate) for all ptosis grades except ptosis grade III. When gland suspension was compared with ptosis equivalent control groups, gland suspension was associated to a higher upper pole volume increment and higher pole convexity and lower pole morphometry. Conclusion: The addition of gland suspension to implant dual plane breast augmentation appears to be a clinically beneficial maneuver with measurable contour impact and appears to avoid subsequent mastopexy procedures, except for high ptosis grade candidates. Abstract : Supplemental Digital Content is available in the text.